Fungsi Manajemen POAC pada Literasi Kopi UPT Perpustakaan Proklamator Bung Karno - Purwanto, Hery; Arisyahidin, Arisyahidin (Universitas Islam Kadiri, 2025)
The library is not only a center of information resources but also a place for self-transformation into a socio-cultural hub by empowering and democratizing the community and local populations in an effort to improve public welfare.